Subtalar and knee joint interaction during running at various stride lengths - Stergiou, N.; Bates, B. T.; Kurz, M. J. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: It has been suggested that during running proper coordination between subtalar pronation/supination and knee flexion/extension via tibial rotation is important to attenuate ground reaction impact forces (GRIF). Lack of coordination over time may produce a wide range of injuries. It was hypothesized that increasing stride length would result in higher GRIF. It was also hypothesized that alterations in stride length would result in changes of the subtalar/knee coordination. Methods: Six subjects ran under 3 different stride lengths (normal stride, understride and overstride) at their self-selected pace. Sagittal, rear view kinematic data and GRIF kinetic data were collected. The subtalar/knee coordination was evaluated via timing and relative velocity measures. Repeated measures ANOVA were performed on these measures with a Tukey post-hoc analysis conducted where appropriate (p<0.01). Results: Increased stride length produced significant increases in GRIF and significantly augmented the differences between rearfoot and knee angular velocities. A change in the rearfoot angle curve from a unimodal (1 minimum) to a bimodal (2 minimums) parabolic configuration was also observed. The appearance of the additional minimum was attributed to the increased impact with the ground. Conclusion: The results indicated that increases in GRIF via changes in stride length could disrupt the coordination between subtalar and knee joint actions.